Optimization Strategy of Competitive Advantage and Sustainable Corporate Performance - Rachmadi, Moch Faizal; Prajanti, Sucihatiningsih Dian Wisika; Widiyanto, Widiyanto (Journal of Economic Education, 2024)
Cooperatives are a sector that has an important role in the national economy. The existence of cooperatives must continue to be improved and preserved, one of which is the Dukuhseti Indonesian Farmer Producer Cooperative (KPPI). Therefore, a business strategy is needed with integrated, integrated and sustainable implementation of competitive advantage and sustainable corporate performance. This research aims to analyze the role of competitive advantage and sustainable corporate performance at KPPI Dukuhseti, analyze the roles and interactions of actors/stakeholders and develop strategic priorities. The research method used is mixed method with analysis using qualitative descriptive, Matrix of Alliance, Conflicts, Tactics, Objectives and Recommendations (MACTOR) and Analytic Network Process (ANP). The research results show that there is a large contribution/role of competitive advantage in corporate sustainable performance. The competitive advantage strategy used focuses on differentiation. Apart from that, in the MACTOR analysis there are 4 main actors, namely KPPI Dukuhseti, the Cooperatives and MSMEs Service, the Food Security Service and Academics. There are also 2 significant goals, namely increasing digital literacy and synergistic development of cooperatives. Meanwhile, ANP analysis shows that environmental criteria and then technology are the main priorities. Regarding alternative policies that are also a priority is increasing digital literacy.